Family Preventive Efforts in Reducing the Impact of Technology Advances in the Digital Age on Early Childhood - Nashir, Muhammad Ja'far; Wardani, Anita; Fajrin, Rara Intan Mutiara; Widayanti, Wahyu; Orlando, Orlando (STKIP Singkawang, 2024)
This study aimed to find out what preventive methods are used by families at home to reduce the negative impacts of technological developments in the digital era. The method used in this research was a qualitative descriptive approach involving 9 parents of children aged 4-8 in Sukoharjo. Semi-structured interview techniques were used for data collection. The data analysis technique used data reduction, data presentation, and data verification. The results showed that parents' preventive efforts to mitigate the impact of technology on children include making rules of use by setting time limits on the use of electronic devices, providing healthy and wise examples in using technology tools, encouraging children's outdoor activities, monitoring content consumed by children, encourage open communication with their children by talking about the dangers and benefits of technology openly, teaching digital literacy by teaching children about privacy, online security, and digital ethics, making a daily schedule that balances screen time and other activities, promoting their hobbies and interests, and keeping pace with technological developments.